Physiography of the North Permian Basin margin: new insights from 3D seismic reflection data - Jackson,CAL; Lewis,MM (Journal of the Geological Society, 2013)
3D seismic reflection data from the Egersund Basin, offshore Norway image geomorphic features that record mid-Permian, footwall degradation of basin-bounding fault systems. This ancient landscape was subsequently flooded during the pan-European, Late Permian transgression of the North Permian Salt Basin, and was fossilised beneath Zechstein Supergroup evaporites. We provide the first conclusive evidence for pre-Zechstein normal faulting in the Egersund Basin, indicating that extensional strain was shared between Permian and Late Jurassic-to-Early Cretaceous rift events.